2016
DOI: 10.1667/rr14408.1
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant Thrombomodulin (Solulin) Ameliorates Early Intestinal Radiation Toxicity in a Preclinical Rat Model

Abstract: Intestinal radiation toxicity occurs during and after abdominopelvic radiotherapy. Endothelial cells play a significant role in modulating radiation-induced intestinal damage. We demonstrated that the endothelial cell surface receptor thrombomodulin (TM), a protein with anticoagulant, antiinflammatory and antioxidant properties, mitigates radiation-induced lethality in mice. The goal of this study was to determine whether recombinant TM (Solulin) can protect the intestine from toxicity in a clinically relevant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 55 publications
(58 reference statements)
0
12
0
Order By: Relevance
“…Radiation-induced expression of E-selectin in human EC lines is dose- and time-dependent, can occur after doses as low as 0.5 Gy, and can occur independent of cytokine activation (36) . Exposure of buccal mucosal samples to 60 Gy prompted an increase in expression of ICAM-1 and E-selectin but not VCAM over baseline levels (37) . All of these adhesion molecules are known mediators of acute and chronic inflammatory reactions and promote macrophage recruitment to ECs.…”
Section: Radiation Effects On Cell Adhesion Molecules and Vascular Homentioning
confidence: 93%
“…Radiation-induced expression of E-selectin in human EC lines is dose- and time-dependent, can occur after doses as low as 0.5 Gy, and can occur independent of cytokine activation (36) . Exposure of buccal mucosal samples to 60 Gy prompted an increase in expression of ICAM-1 and E-selectin but not VCAM over baseline levels (37) . All of these adhesion molecules are known mediators of acute and chronic inflammatory reactions and promote macrophage recruitment to ECs.…”
Section: Radiation Effects On Cell Adhesion Molecules and Vascular Homentioning
confidence: 93%
“…155 By using a pharmacological strategy to activate this pathway, mitigation of radiation toxicity was achieved in a relevant model of RT in which a loop of rat small bowel was exposed to nine daily doses of 5 Gy. 156 On the other hand, the targeting of CD47, a thrombospondin-1 receptor, has demonstrated that inhibiting CD47 signalling maintains the viability of normal tissues following irradiation, likely through radioprotection of endothelial cells, while increasing the radiosensitivity of tumours. 157 Also, an angiopoietin-1 mimic significantly reduces skin radiation toxicity, potentially by increasing survival and function of irradiated endothelial cells through tyrosine kinase with immunoglobulin and epidermal growth factor homology domains 2 (Tie2) receptor activation.…”
Section: Endothelial-oriented Strategies For Therapeutic Gain In Radimentioning
confidence: 99%
“…162 The use of anticoagulants such as heparin has been investigated, but the results to date have been mostly insignificant and generally inconsistent. 163 In contrast, the TM-APC pathway is a hopeful target for preventing or treating radiation toxicity in normal tissues using strategies aimed at restoring or preserving endothelial TM or replacing protein C. 156,164,165 Also, thrombin inhibition has been investigated as a strategy to minimise the side-effects of RT. The recombinant thrombin inhibitor hirudin has shown a protective effect against small bowel radiation toxicity in a model of localised small bowel radiation in rats.…”
Section: Decreasing Coagulopathymentioning
confidence: 99%
“…By forming a complex with the coagulation factor thrombin, TM can exert beneficial effects via generation of activated protein C (APC) (47). Ionizing radiation negatively affects TM expression (48,49), while activation of the APC pathway and administration of exogenous recombinant TM protect against radiation toxicity (50,51). γ-Tocotrienol induces the expression of TM in primary and immortalized human endothelial cells (45).…”
Section: Tocotrienols Are Potent Radiation Protectorsmentioning
confidence: 99%